(untitled) (Journal of Universal Science Research, 2025)
The need to provide food and drinking water to the world’s population is developing urgently due to the planet’s rapidly expanding population and the loss of arable and irrigated land. At the start of the twenty-first century, this issue is still unsolved despite the tremendous advancements in agriculture and cattle farming. Increasing the productivity of livestock, poultry, and fish farming as well as the production of agricultural products is one of the best strategies to address this issue. The production and variety of potassium and NPK fertilizers without chlorine, as well as feed calcium phosphates, are on the rise in practically all industrialized nations worldwide.